AN ANALYSIS OF ENGLISH ABSTRACTS WRITTEN BY UNDERGRADUATE STUDENTS OF TANJUNGPURA UNIVERSITY - Shilvani Shilvani; Sudarsono Sudarsono; Yohanes Gatot Sutapa Yuliana (STKIP Persada Khatulistiwa Sintang, 2023)
This research aimed to identify grammatical errors encountered in the undergraduate theses abstracts written by students at Tanjungpura University. This research applied the descriptive method. The data were collected with the purposive sampling technique. The subjects numbered 20 abstracts published in 2021; they were analyzed employing the error analysis technique. The findings showed that the students made errors classified into omission, misinformation, addition, and misordering. The most frequent errors made by the students were omission (52.9%), and the least frequent ones were addition and misordering, each of which occurred (5.88%). Of 20 abstracts, only five were without errors; others contained errors.